Application of the multivariate statistical analisis in investigation long-term durability of polymers. 2. Calculating experiment. - A. A. Valishin; T. S. Stepanova (Тонкие химические технологии)
The method of construction of optimum regressive model of temperature-temporary dependence, basing on principles of multivariate regressive analyses was proposed. Calculating experiment, simulating real conditions of tests of durability was carried out and quasi-experimental data, which were exposed statistical processing by the use of proposed method, were received. Reality of effect of displacement of pole was proved and, thus, old controversy on the occasion of this effect was finished. After the example of polymers polyethylene and polymethylmetacrilat it was showed, that of temperature-temporary dependence of polyethylene is described by model of Jurkov and temperature-temporary dependence of polymethylmetacrilat - by model of Regel-Ratner with displacement of pole.